The Combination of Natural Music Therapy and Rose Aromatherapy Lowers Blood Pressure in Hypertensive Patient - Saparudin, Hilmalana; Armiyati, Yunie; Khoiriyah, Khoiriyah (Universitas Muhammadiyah Semarang, 2020)
The incidence of hypertension is increasing, followed by high complications and mortality due to hypertension. Blood pressure control is needed to improve the quality of life of hypertensive patients, including non-pharmacological management. One of the non-pharmacological hypertension management is a combination of natural music therapy and rose aromatherapy. The purpose of this study was to analyse the effect of combination of natural music therapy and rose aromatherapy on reducing blood pressure in hypertensive patients in the Kedungmundu area of Semarang. The research design was Quasy Experiment research, one group pretest and posttest design. Sample of 16 respondents were selected by random sampling. The result showed that the combination of natural music therapy and rose aromatherapy was effective in reducing blood pressure in hypertensive patients (p value = 0.000). The recommendation of this study is that a combination of natural music therapy and rose aromatherapy can be chosen as an alternative nursing intervention in reducing blood pressure in hypertensive patients.